Contraceptive trajectories postpartum: A longitudinal qualitative study of women living with HIV in Cape Town, South Africa. (January 2022) - McTigue, Georgiana; Swartz, Alison; Brittain, Kirsty; Rini, Zanele; Colvin, Christopher J.; Harrison, Abigail; Myer, Landon; Pellowski, Jennifer
Abstract: Background: Supporting the ability of women living with HIV (WLWH) to avoid unintended pregnancy during the postpartum period decreases the number of new pediatric HIV infections, reduces pregnancy-related morbidity and mortality, and is a cost-effective strategy for the elimination of mother-to-child transmission. However, little is currently known about the contraceptive intentions and experiences of reinitiating family planning use among mothers living with HIV as they transition from pregnancy into postpartum. Study objectives: To (1) understand the contraceptive trajectories of women living with HIV during pregnancy and postpartum in Cape Town, South Africa, and (2) identify factors shaping differing contraceptive trajectories during the postpartum period. Methods: Thirty pregnant WLWH were interviewed during their eighth month of pregnancy and completed follow-up interviews at 6–8 weeks and 9–12 months postpartum ( n  = 81 total interviews). Interview topics included postpartum contraception intentions, contraceptive use, and experiences accessing family planning services. Trajectory analysis of contraceptive intentions was applied after initial thematic coding. Results: While nearly half of women interviewed during pregnancy expressed an intention to utilize a non-injectable contraceptive option after childbirth (e.g. implant, IUD, sterilization, oral contraceptive pills), all women interviewed at one year postpartum had received at least one injection. Three main contraceptive trajectories were identified. (1) realization of contraceptive intentions postpartum; (2) unrealized contraceptive intentions postpartum; and (3) change in contraceptive intention over time. Provider influence, coordination of services, and low contraceptive inventory were identified as potential factors shaping the contraceptive trajectories of participants enrolled in the study. Conclusion: Disparities between contraceptive method intentions articulated by WLWH during pregnancy and methods attained postpartum suggest that significant barriers remain for women who are unsatisfied with injectable contraception. Failing to provide postpartum mothers living with HIV their intended family planning method undermines efforts to prevent unintended pregnancy, a key pillar of elimination of mother-to-child transmission. Highlights: Contraceptive intentions of pregnant women living with HIV were traced postpartum. A trajectory approach was used to analyze longitudinal qualitative data. All women received the injection postpartum, regardless of their method intention. Provider influence, care coordination, and inventory impacted method trajectories.